FINANCING OF LOCAL BUDGETS ON THE EXAMPLE OF IVANO-FRANKIVSK REGION - I. Kokhan (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu, 2019)
The dominant tendencies of the current stage of development of the national economy are the strengthening of processes of regionalization, which involve shifting attention in decision-making on socio-economic development to the regional level, with a simultaneous shift of emphasis to the discovery of internal potential. On the other hand, new challenges caused by global and international imbalances, which negatively affect the socio-economic development of Ukrainian regions, are a barrier that prevents local governments from pursuing an independent development policy. In this context, the reform processes of public finances currently experienced by Ukraine are relevant and require rethinking the patterns of influence of financial policy instruments and levers on the socio-economic development of the regions.